Eye Black Circle of Milkfish Segmentation on Hsv Color Space - Eko Prasetyo (Fakultas Teknik Universitas Bhayangkara, 2018)
One of the popular fish consumed by the people is milkfish. The freshness of milkfish can be observed from eyecondition. maka segmentasi lingkatan hitam mata ikan bandeng penting dilakukan we conduct experiment in milkfishimage segmentation to get region of interest in eye circle. Kami mengusulkan frame work untuk segmentasilingkaran mata ikan bandeng menggunakan filter spasial pada komponen Hue dan Value ruang warna HSV. Byusing 10 milikfish images, we get segmentation performance with average of precision 84.04%. But we get badperformance in recall, because achieve recall 43.08%.